Analisis Peran Bank terhadap Pemberdayaan UMKM melalui Pembiayaan Murabahah - Dyah Ayu Puspita; Al Haq Kamal (Journal of Islamic Entrepreneurship and Business Research, 2025)
Islamic banks operate based on Sharia principles, emphasizing justice, transparency, and the prohibition of riba. These principles provide a positive impact in supporting the development of micro, small, and medium enterprises (MSMEs) in Indonesia. One of the key financing schemes offered by Islamic banks is murabahah, which plays a crucial role in MSME empowerment. This study aims to analyze the role and impact of murabahah financing by Islamic banks on MSME development. The research employs a qualitative descriptive approach to assess how this financing scheme contributes to MSME growth. The findings indicate that Islamic banks significantly enhance MSME performance, as evidenced by increased revenue, workforce expansion, and higher value-added production. The results highlight the effectiveness of murabahah financing in fostering MSME sustainability, promoting economic inclusion, and supporting financial stability. This study contributes to the existing literature by providing empirical insights into the relationship between Islamic banking and MSME development. Furthermore, it underscores the importance of Sharia-compliant financial instruments in addressing the financial needs of MSMEs while adhering to ethical and religious principles. The study’s findings can serve as a reference for policymakers and financial institutions in designing more effective Sharia-based financing models to enhance MSME resilience and competitiveness in the market.